The business environment - Wetherly Paul (Oxford: Oxford University Press, 2023)
A range of themes is clearly presented in each chapter to ensure this approach does not over-simplify the presentation of the business environment. These themes are designed to demonstrate to the reader that business is diverse and complex and there are many inter-relationships between the environments. The themes also outline the factors which influence business, for example the diversity of business, the complexity of the external environment, and the interaction between business and its environment